Digital resources in cartographic literacy and geography teaching (Revista Internacional de Formação de Professores, 2022)
The presence of technologies is increasingly recurrent in everyday life, including in the school environment and in pedagogical work. Digital resources contribute to the teaching and learning process and can help to understand and represent the geographic space. In this way, this study constitutes a survey of dissertations and theses produced in Brazil between 2013 and 2020. Its purpose is to present an overview of research that addresses the proposed theme. Bibliometrics was used as a methodology. At the end of the investigation, it was concluded that technologies help in learning. However, there are aspects that directly interfere in the quality and efficiency of the use of digital resources in classes.
Keywords: Digital resources. Cartographic literacy. Geography teaching. Learning.